Toward ontology‐based risk management framework for software projects: An empirical study. Issue 12 (24th June 2020) - Abioye, Temitope Elizabeth; Arogundade, Oluwasefunmi Tale; Misra, Sanjay; Akinwale, Adio T.; Adeniran, Olusola John
Abstract: Software risk management is a proactive decision‐making practice with processes, methods, and tools for managing risks in a software project. Many existing techniques for software project risk management are textual documentation with varying perspectives that are nonreusable and cannot be shared. In this paper, a life‐cycle approach to ontology‐based risk management framework for software projects is presented. A dataset from literature, domain experts, and practitioners is used. The identified risks are refined by 19 software experts; risks are conceptualized, modeled, and developed using Protégé. The risks are qualitatively analyzed and prioritized, and aversion methods are provided. The framework is adopted in real‐life software projects. Precision recall and F‐measure metrics are used to validate the performance of the extraction tool while performance and perception evaluation are carried out using the performance appraisal form and technology acceptance model, respectively. Mean scores from performance and perception evaluation are compared with evaluation concept scale. Results showed that cost is reduced, high‐quality projects are delivered on time, and software developers found this framework a potent tool needed for their day‐to‐day activities in software development. Abstract : This work showcase the design and implementation of ontology based risk management framework that will serves as bedrock for developing efficient software projects using software life cycle approach. The replacement of the present way of software risk management (documentation procedure) with semantic web technology called ontology which will enhance the development of quality software projects. Promotion of knowledge reuse which will serve as reference for future work.